(untitled) (Research, Society and Development, 2020)
The objective of the work was to evaluate the effectiveness of pre-germinative treatments on seeds and emergence of G. acuminata seedlings. The experiment was carried out at the Fruit Laboratory of Embrapa Amazônia Oriental, Belém, Pará. It was conducted in a protected environment and devoid of temperature and relative humidity controls. The water content was determined using the oven method at 105±3 ºC, using four samples of ten seeds before and after application of the treatments. A completely randomized design in a factorial (2 x 5) was adopted, being: seed treatments (with and without tegument) and soaking levels (without soaking, soaking in distilled water, soaking in concentrations of 200, 400 and 600 mg.L-1 AG3 for 24 hours), with four replications of 50 seeds each. Percentage of emergence, emergence speed index, mean time of emergence, dry mass of the aerial part, dry mass of the root, length of the aerial part and length of the root were evaluated. The means obtained in the experiment were compared using the Scott-knott test at the level of 5% probability. The soaking of seeds with or without tegument, in an AG3 solution at concentration of 600 mg.L-1 for 24 hours, accelerates the germination process of the seeds and emergence of G. acuminata seedlings. The removal of the tegument and the soaking in AG3 is required to accelerate and uniform the germinative process of G. acuminata seeds.